Complications of Allogeneic Hematopoietic Stem Cell Transplantation. (9th August 2014) - Arnaout, Karim; Patel, Nihar; Jain, Maneesh; El-Amm, Joelle; Amro, Farah; Tabbara, Imad A.
<x xml:space="preserve">Abstract</x> Infection, graft-versus-host disease (GVHD), and to a lesser extent sinusoidal obstructive syndrome (SOS) represent the major causes of morbidity and mortality in patients undergoing allogeneic hematopoietic stem cell transplantation (AHSCT). During the last decade, progress in prevention and treatment of these complications led to improvement in the outcome of these patients. Despite the fact that nonmyeloablative regimens have been increasingly used in elderly patients and in patients with co-morbidities, the nonrelapse related mortality remains a challenge and long-term follow-up is required. The objective of this manuscript is to provide an updated concise review of the complications of AHSCT and of the available treatment interventions.